ANALISIS TINGKAT KESEHATAN BANK PERKREDITAN RAKYAT (BPR) DENGAN METODE CAMEL (STUDI KASUS PADA BPR RASUNA PONOROGO PERIODE 2007-2010) - Hartono, Arif (Widya Warta, 2015)
The objective of this research is to assess the financial performance of BPR Rasuna. The data were collected applying Â documentation method in the form of financial statements of 2007-2010. The data analysis made use of CAMEL method. The results showed that the financial performance of BPR Rasuna was good as the credit score of CAMEL obtained was above 81 (the minimumÂ  limit).